Prevalence of malnutrition among old age people in Africa - Seid, Ahmed Muhye; Babbel, Netsanet Fentahun (Frontiers in Aging, 2022)
Abstract Background: Improved health care and rising life expectancy are creating a growing pool of old age people all over the world, including Africa. Malnutrition in the old age people is associated with both short- and long-term negative health outcomes. However, the reported burdens of malnutrition are fragmented and inconsistent, where more compiled evidence is warranted to aid decision-makers. Hence, this paper is aimed to estimate the pooled prevalence of malnutrition among old age people in Africa. Methods: A systematic search for research reporting the prevalence of malnutrition among old age people (aged above 60 years) was conducted from HINARI/PubMed and Google Scholar databases using combination keywords. Published articles in English language starting from January 2000 to October 2021 were screened. We presented the results based on the standard for reporting systematic review and meta-analysis of observational studies. A random-effect meta-analysis was done to estimate the prevalence of malnutrition along with the 95% confidence intervals. The publication bias was assessed using the funnel plot. Results: A total of 1,442 studies were retrieved based on the search strategy, where only 36 studies (n = 15,266 participants) reported from 11 African countries were included for meta-analysis. The reported prevalence of malnutrition ranges from 2.2 to 77.3% across Africa. Overall, the pooled prevalence of malnutrition was 18% (95% CI: 15-22; I2 = 98.1; p < 0.001). The prevalence is higher in the Central Africa (3.8%; 95 % CI: 3.2-4.4), in the community (3.1 %; 95 % CI: 2.7-3.7), and among advanced age (3.5 %; 95 % CI: 2.3-5.4). Conclusion: The prevalence of malnutrition in African old age people is high and differs by setting, assessment tool, and country of residence. Hence, due attention to geriatric nutrition is mandatory, and the need for a valid, reliable, and simple screening tool should be thought of.